EVALUASI KINERJA GURU DALAM PEMBELAJARAN DI SDN KETAPANG 03 DENGAN MODEL CHARLOTTE DANIELSON - Nuvita Sari, Ela; Suhandi Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate teacher performance in learning at SDN Ketapang 03 using the Charlotte Danielson model. Employing a quantitative evaluative research approach, the study assesses four key aspects of teacher performance: planning and preparation, classroom management, instruction, and professional responsibilities. The results indicate that teachers achieved a performance score of 87% in planning and preparation, 89% in classroom management, 75% in instruction, and 73% in professional responsibilities. This research provides valuable insights for enhancing teacher effectiveness and overall education quality.